Synthesis, Characterization and Applications of Antimicrobial Materials - Mustafa, Faisal Suleiman Khalil (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Three distinct materials were synthesised, characterized, and tested as antibacterial agents in this thesis. The ability of the synthesised materials to decontaminate polluted water was also studied. Firstly (in chapter 1), a novel compound ({[1,3-bis(2,4,5-trichlorophenoxy) propan-2- yl] oxy}-3-(2,4,5-trichlorophenoxy) hexan-2-ol) (TPTH) was synthesized and characterized. Biological evaluation of the compound was investigated by performing an antimicrobial activity and cytotoxic assays. The compound displayed good antimicrobial activity with minimum inhibition concentration detected as 0.02μg/mL, 0.08μg/mL and 0.15μg/mL against Methicillin Sensitive Staphylococcus Aureus (MSSA), Methicillin Resistant Staphylococcus Aureus (MRSA) and Escherichia coli (E. coli) respectively. Additionally, a well diffusion assay demonstrated that the zone of inhibition of S. aureus, MRSA and E. coli was 24 mm, 22 mm and 18 mm respectively. MTT assay results revealed that, at a range of effective anti-microbial concentrations, TPTH is non-toxic against stem cells. Secondly (in chapter 2), ethylenediamine-epichlorohydrin-trichlorophenol (EET) crosslinked polymer was synthesized and characterized. EET exhibited substantial antibacterial activity with inhibition zones of 38 and 64 mm against E. coli and S. Aureus bacteria. Therefore, it was applied to treat methyl orange (MO) and rhodamine B (RB) dyes containing synthetic aqueous solutions under varying operation parameters. Notably, 10 and 15 mg of EET removed 98.72 % of MO at pH 8 and 92.45% of RB at pH 3. The EET demonstrated a fast adsorption rate and the adsorption data fit well with the pseudo-second-order for both dyes, suggesting chemisorption. Also, considering the correlation coefficient values, the experimental dataset fit suitably with the Temkin equation for RB and Langmuir equation for MO. Lastly (in chapter 3), novel Li doped Zn0.5Ni0.5Fe2O4 (Li/ZNF) photosensitive catalyst was prepared to degrade toxic antiseptic 2,4,5-trichlorophenol (TCP) and inhibit bacteria. Characterization of Li/ZNF nanoparticles revealed it possesses a bandgap of 2.89 eV, exhibited a total pore volume of 0.298 cm3 /g with a crystallite size and percent crystallinity of 16.9 nm and 76.8% respectively. Degradation of TCP (50 ppm) with 10 mg Li/ZNF under optimized conditions (pH 3, 4 mM H2O2 and 353 nm UV- light) reached 80% after 6 h with a degradation rate constant of 0.0019 min-1 . The efficiency of reusable Li/ZNF composite to degrade 50 ppm TCP decreased by 14% after the fifth cycle. According to the antibacterial tests; 15 and 25 mg of Li/ZNF were sufficient to completely inhibit both S. aureus and E. coli bacteria under UV and dark (without UV light) conditions, respectively. The photocatalytic mechanism was established based on the active radical quenching tests which revealed the contribution of •OH and •O2 - radicals.

ÖZ: Bu tezde üç farklı materyal sentezlenmiş, karakterize edilmiş ve antibakteriyel ajan olarak test edilmiştir. Sentezlenen malzemelerin kirli suyu dekontamine edebilme özeliği de incelenmiştir. İlk olarak (1. bölümde), yeni bir madde ({[1,3-bis(2,4,5-triklorofenoksi) propan-2- il]oksi}-3-(2,4,5-triklorofenoksi) heksan-2-ol) (TPTH ), sentezlendi ve karakterize edildi. Maddenin biyolojik değerlendirmesi, antimikrobiyal aktivite ve sitotoksik testler yapılarak araştırıldı. Metisiline Duyarlı Staphylococcus Aureus (MSSA), Metisiline Dirençli Staphylococcus Aureus (MRSA) ve Escherichia coli'ye (E. coli) karşı iyi antimikrobiyal aktivite sergileyen bileşiğin, sırası ile minimum inhibisyon konsantrasyonları 0.02μg/mL, 0.08μg/mL ve 0.15μg/mL olarak bulunmuştur. Ek olarak, kuyu difüzyon analizi, S. aureus, MRSA ve E. coli'nin inhibisyon bölgesinin sırasıyla 24 mm, 22 mm ve 18 mm olduğunu göstermiştir. MTT analizi, bir dizi etkili anti-mikrobiyal konsantrasyonda TPTH'nin kök hücrelere karşı toksik olmadığını ortaya koydu. İkinci olarak (2. bölümde), etilendiamin-epiklorohidrin-triklorofenol (EET) çapraz bağlı polimer sentezlendi ve karakterize edildi. EET, E. coli ve S. Aureus bakterilerine karşı 38 ve 64 mm'lik inhibisyon bölgeleri ile önemli antibakteriyel aktivite sergiledi. Bu nedenle, sentetik sulu çözeltiler içeren metil oranj (MO) ve rodamin B (RB) boyalarının değişen çalışma parametreleri altında incelenmesi uygun bulunmuştur. Özellikle, 10 ve 15 mg EET, pH 8'de MO'nun %98.72'sini ve pH 3'te RB'nin %92.45'ini emmiştir. EET, hızlı bir adsorpsiyon grafiği göstermiş ve adsorpsiyon verileri, her iki boya için yalancı ikinci derece kinetiğine uyduğu ve bu da ortamda kimyasal absorpsiyon gerşekleştiğini göstermektedir. Ayrıca, korelasyon katsayısı değerleri dikkate alındığında, deneysel veri seti, RB için Temkin denklemine ve MO için Langmuir denklemine uymaktadır. Son olarak (3. bölümde), toksik antiseptik 2,4,5-triklorofenol'ü (TCP) parçalamak ve bakterileri inhibe etmek için yeni Li katkılı Zn0.5Ni0.5Fe2O4 (Li/ZNF) ışığa duyarlı katalizör hazırlandı. Li/ZNF nanoparçacıklarının karakterizasyonu, katalizörün 2.89 eV'lik bir bant aralığına sahip olduğunu, kristalit boyutu ve yüzde kristallik sırasıyla 16.9 nm ve %76.8 olduğu, 0.298 cm3 /g toplam gözenek hacmi sergilediğini ortaya çıkardı. Optimize edilmiş koşullar altında (pH 3, 4 mM H2O2 ve 353 nm UV ışığı) 10 mg Li/ZNF ile TCP'nin (50 ppm) bozunması, 0,0019 dk-1 bozunma oranı sabiti ile 6 saatın sonunda %80'e ulaştı. Yeniden kullanılabilir Li/ZNF kompozitinin 50 ppm TCP'yi azaltma verimliliği, beşinci döngüden sonra %14 azaldı. Antibakteriyel testlere göre; 15 ve 25 mg Li/ZNF, sırasıyla UV ve karanlık (UV ışığı olmadan) koşullar altında hem S. aureus hem de E. coli bakterilerini tamamen inhibe etmek için yeterli bulunmuştur. Fotokatalitik mekanizma, •OH ve •O2 - radikallerinin katkısını ortaya koyan aktif radikal söndürme testleriyle incelenmiştir.
Doctor of Philosophy in Chemistry. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2021. Co-Supervisor: Assoc. Prof. Dr. Mümtaz Güran and Supervisor: Prof. Dr. Mustafa Gazi.
Keywords: Thesis Tez; Chemistry Department; Antimicrobial Materials; Medicinal Plants; Health aspects; Trichlorophenol; epichlorohydrin; antimicrobial; antiseptic; non-toxic; dye adsorption; polymer; thermodynamic; ternary photocatalyst; degradation; Li -doped Zn-Ni ferrites.